NOACs Added to WHO's Essential Medicines List: Recommendations for Future Policy Actions - Mariachiara Di Cesare; Jordan D. Jarvis; Oana Scarlatescu; Xinyi Leng; Ezequiel J. Zaidel; Esteban Burrone; Jean-Luc Eiselé; Dorairaj Prabhakaran; Karen Sliwa (Ubiquity Press, 2020)
The introduction of non-vitamin K antagonists oral anticoagulants, a class of medicines which includes dabigatran, apixaban, edoxaban and rivaroxaban, has resulted in improvements in the safety and efficacy of non valvular atrial fibrillation treatment for stroke prevention, with significant reductions in stroke, intracranial haemorrhage, and mortality. For these reasons, a team of World Heart Federation Emerging Leaders led efforts to add non-vitamin K antagonists oral anticoagulants to the World Health Organization's Model List of Essential Medicines in 2019. Following the inclusion of this class of medicines in the Essential Medicines List, this editorial proposes several recommendations to improve the accessibility, affordability and acceptability of non-vitamin K oral anticoagulants, especially in low- and middle-income settings, in order to successfully manage non-valvular atrial fibrillation and to lower the risk of stroke.